HADLANAH ANAK BELUM MUMAYYIZ DIASUH AYAH DALAM PUTUSAN PENGADILAN AGAMA KRAKSAAN - Subyanto Subyanto; Subaidi Subaidi (Fakultas Syariah dan Ekonomi Islam, Universitas Ibrahimy, 2025)
This study examines the granting of custody rights (hadhanah) of a child whohas not yet reached the age of mumayyiz to the father based on a decision ofthe Kraksaan Religious Court, which in principle differs from the generalprovisions of Islamic law and the Compilation of Islamic Law (KHI) thatprioritize the mother as the primary caregiver. The background of this researcharises from the reality of divorce that produces legal consequences concerningchild custody, where the best interest of the child must become the primaryconsideration in determining guardianship rights. This research aims toanalyze the legal considerations used by judges in granting custody to thefather and to assess their conformity with Islamic law perspectives andapplicable legal regulations. The study employs a qualitative field researchmethod, utilizing primary data obtained from field findings and secondarydata from literature, classical fiqh texts, and related legal sources.The findings indicate that although normatively a child who has not yetreached mumayyiz age is entitled to maternal custody, such rights may beforfeited if the mother fails to meet the qualifications of a proper guardian(hadhin), such as abandoning the child, failing to appear in court proceedings,or being unable to ensure the child’s physical and psychological welfare. Inthe case examined, the judge granted custody to the father after consideringtrial facts demonstrating that the mother had left the child and did not showresponsibility for caregiving. This decision was grounded in the MarriageLaw, the KHI, and the opinions of Islamic jurists emphasizing that the child’swelfare and best interest constitute the primary principle in custodydetermination.In conclusion, the judicial decision granting custody to the father does notcontradict Islamic law insofar as it is based on the child’s welfare and themother’s unfitness as a caregiver. This study underscores that the protectionand well-being of the child must remain the central orientation in resolvingcustody disputes, beyond general normative assumptions.Keywords: